Digital Single-operator Cholangioscopy (DSOC) Improves Interobserver Agreement (IOA) and Accuracy for Evaluation of Indeterminate Biliary Strictures: The Monaco Classification. Issue 2 (7th February 2022) - Sethi, Amrita; Tyberg, Amy; Slivka, Adam; Adler, Douglas G.; Desai, Amit P.; Sejpal, Divyesh V.; Pleskow, Douglas K.; Bertani, Helga; Gan, Seng-Ian; Shah, Raj; Arnelo, Urban; Tarnasky, Paul R.; et al.
Abstract : Background: Visual characteristics seen during digital single-operator cholangioscopy (DSOC) have not been validated. The aim of this 2-phase study was to define terminology by consensus for the visual diagnosis of biliary lesions to develop a model for optimization of the diagnostic performance of DSOC. Materials and Methods: In phase 1 (criteria identification), video-cholangioscopy clips were reviewed by 12 expert biliary endoscopists, who were blinded to the final diagnosis. Visual criteria were consolidated into the following categories: (1) stricture, (2) lesion, (3) mucosal features, (4) papillary projections, (5) ulceration, (6) abnormal vessels, (7) scarring, (8) pronounced pit pattern. During the second phase (validation), 14 expert endoscopists reviewed DSOC (SpyGlass DS, Boston Scientific) clips using the 8 criteria to assess interobserver agreement (IOA) rate. Results: In phase 1, consensus for visual findings were categorized into 8 criteria titled the "Monaco Classification." The frequency of criteria were: (1) presence of stricture—75%, (2) presence of lesion type—55%, (3) mucosal features—55%, (4) papillary projections—45%, (5) ulceration—42.5%, (6) abnormal vessels—10%, (7) scarring—40%, and (8) pronounced pit pattern—10%. The accuracy on final diagnosis based on visual impression alone was 70%. In phase 2, the IOA rate using Monaco Classification criteria ranged from slight to fair. The presumptive diagnosis IOA was fair (κ=0.31, SE=0.02), and overall diagnostic accuracy was 70%. Conclusions: The Monaco classification identifies 8 visual criteria for biliary lesions on single-operator digital cholangioscopy. Using the criteria, the IOA and diagnostic accuracy rate of DSOC is improved compared with prior studies.